2010
DOI: 10.3109/00952990.2010.540278
|View full text |Cite
|
Sign up to set email alerts
|

Delay-discounting among homeless, out-of-treatment, substance-dependent men who have sex with men

Abstract: A better understanding of the prevalence of delay-discounting type behaviors among homeless, substance-dependent MSM can be used to inform the development of tailored substance abuse interventions for this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Hence, rates of monetary delay discounting are correlated with sexual behavior that is risky. Furthermore, higher rates of discounting than those of healthy controls are found in individuals who already have HIV (Dierst-Davies et al, 2011) or hepatitis C (Huckans et al, 2011). …”
Section: Research On the Discounting Of Delayed Reinforcersmentioning
confidence: 99%
“…Hence, rates of monetary delay discounting are correlated with sexual behavior that is risky. Furthermore, higher rates of discounting than those of healthy controls are found in individuals who already have HIV (Dierst-Davies et al, 2011) or hepatitis C (Huckans et al, 2011). …”
Section: Research On the Discounting Of Delayed Reinforcersmentioning
confidence: 99%
“…However, the vast majority of participants in previous studies selected only opposite gender partners on the SDT, making it unclear whether the aforementioned findings generalize to choices MSM make about condom use with male partners. Indeed, there are no published reports that examine discounting of condom-protected sex or any other HIV-related outcomes among MSM, and to our knowledge, only two studies have examined discounting of any commodity (money) among MSM (13, 23). Taken together, these studies demonstrated associations between steeper discounting of delayed monetary rewards and substance dependence (13) and higher rates of UAI (23) among MSM, and acknowledge that future studies that examine relations between discounting and HIV risk among MSM would benefit from using delay discounting tasks specific to sexual risk taking (23), as no such studies exist in the literature, indicating an important opportunity to extend this area of research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using tasks assessing monetary preferences, one recent study found that substance-dependent men who have sex with men (MSM) exhibit significantly more impulsive delay discounting compared to a control group [28]. Impulsive monetary discounting has also been shown to be associated with younger age of sexual initiation and recent sexual infidelity in healthy young adults [29], albeit with some methodological ambiguity.…”
Section: Introductionmentioning
confidence: 99%